Impact of high resolution satellite wind vector data on NCMRWF assimilation and forecasting system (MAUSAM, 2003)
High resolution Atmospheric Motion Vector (AMV) data and Ocean surface wind vectors from QuikScat scatterometer have recently become available at NCMRWF. Efforts are on to assimilate these new data sets in Global Data Assimilation and Forecasting (GDAF) system operational at NCMRWF. In this study an attempt is made to quantify the impact of the new data set through an Observational System Experiment (OSE).  The impact has been examined in terms of various objective scores and the circulation features. It is clearly seen that the inclusion of the new data set results in some improvement in the forecast skill, also in reproduction of synoptic circulations in better way.